The nationality of the international judge: Policy options for the Multilateral Investment Court - Catharine Titi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
The nationality of judges on the international bench can impact their decisions by making them partial to their home countries. In light of the efforts to establish a Multilateral Investment Court, this Perspective considers policy options in relation to the nationality of judges, including the institution of ad hoc judges.
Keywords: 330